Smad4 Loss in Esophageal Adenocarcinoma Is Associated With an Increased Propensity for Disease Recurrence and Poor Survival. (April 2015) - Singhi, Aatur D.; Foxwell, Tyler J.; Nason, Katie; Cressman, Kristi L.; McGrath, Kevin M.; Sun, Weijing; Bahary, Nathan; Zeh, Herbert J.; Levy, Ryan M.; Luketich, James D.; Davison, Jon M.
Abstract : Previously regarded as a rare neoplasm, the incidence of esophageal adenocarcinoma has risen rapidly in recent decades. It is often discovered late in the disease process and has a dismal prognosis. Current prognostic markers including clinical, radiographic, and histopathologic findings have limited utility and do not consider the biology of this deadly disease. Genome-wide analyses have identified SMAD4 inactivation in a subset of tumors. Although Smad4 has been extensively studied in other gastrointestinal malignancies, its role in esophageal adenocarcinoma remains to be defined. Herein, we show, in a large cohort of esophageal adenocarcinomas, Smad4 loss by immunohistochemistry in 21 of 205 (10%) tumors and that Smad4 loss correlated with increased postoperative recurrence ( P =0.040). Further, patients whose tumors lacked Smad4 had shorter time to recurrence (TTR) ( P =0.007) and poor overall survival (OS) ( P =0.011). The median TTR and OS of patients with Smad4-negative tumors was 13 and 16 months, respectively, as compared with 23 and 22 months, respectively, among patients with Smad4-positive tumors. In multivariate analyses, Smad4 loss was a prognostic factor for both TTR and OS, independent of histologic grade, lymphovascular invasion, perineural invasion, tumor stage, and lymph node status. Considering Smad4 loss correlated with postoperative locoregional and/or distant metastases, Smad4 was also assessed in a separate cohort of 5 locoregional recurrences and 43 metastatic esophageal adenocarcinomas. In contrast to primary tumors, a higher prevalence of Smad4 loss was observed in metastatic disease (44% vs. 10%). In summary, loss of Smad4 protein expression is an independent prognostic factor for TTR and OS that correlates with increased propensity for disease recurrence and poor survival in patients with esophageal adenocarcinoma after surgical resection.